1995
DOI: 10.1093/bja/74.5.521
|View full text |Cite
|
Sign up to set email alerts
|

Cricoid pressure impedes placement of the laryngeal mask airway

Abstract: We have studied 22 patients to examine whether or not cricoid pressure affects ventilation of the lungs via the laryngeal mask and its correct positioning. In a randomized, crossover design, the laryngeal mask was inserted with or without cricoid pressure applied with a standardized force of 30 N using a cricoid yoke. A standardized pillow (6 cm in height) was placed under the patient's occiput, but the neck was not supported. Ventilation of the lungs via the laryngeal mask was adequate in all patients when no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 20 publications
3
73
0
3
Order By: Relevance
“…In the recent study reported by Asai et al, even single-handed cricoid pressure impeded placement of the LMA when sufficient force was applied. 12 These findings indicate that cricoid pressure should not be used during insertion of the LMA. In some patients, adequate ventilation can be obtained through the LMA during cricoid pressure.…”
Section: Discussionmentioning
confidence: 98%
“…In the recent study reported by Asai et al, even single-handed cricoid pressure impeded placement of the LMA when sufficient force was applied. 12 These findings indicate that cricoid pressure should not be used during insertion of the LMA. In some patients, adequate ventilation can be obtained through the LMA during cricoid pressure.…”
Section: Discussionmentioning
confidence: 98%
“…This is a well-recognised cause of a decrease in temperature following anaesthetic induction [12]. Indeed, the only way that this decrease in core temperature may be avoided is by a period of active warming pre-induction [9,13].…”
Section: Discussionmentioning
confidence: 99%
“…This is a well-recognised cause of a decrease in temperature following anaesthetic induction [12]. Indeed, the only way that this decrease in core temperature may be avoided is by a period of active warming pre-induction [9,13].We have shown that there is a significant decrease in patients' core temperature in the anaesthetic room while intravascular lines, epidural and urinary catheters are inserted. To reduce this temperature decrease, lines and catheters should be placed before induction of general anaesthesia.…”
mentioning
confidence: 83%
“…A prevenção da aspiração pulmonar é fundamental, mas a permeabilidade das vias aéreas deve prevalecer. A ventilação e a oxigenação podem ser facilitadas pelo emprego da máscara laríngea convencional ou da ProSeal ® , mas, de acordo com alguns estudos, a manobra de Sellick dificulta o correto posicionamento de ambos os instrumentos de acesso à via aérea 38,39 . Nesses casos, pode ser necessária a interrupção da manobra temporariamente, o que parece ser uma opção razoável, já que a compressão da cartilagem cricóide pode se tornar ineficaz após poucos minutos de aplicação 40 .…”
Section: Manobra De Sellick Em Situações "Não Ventilo Não Intubo"unclassified